Collaborative-metacognitive use of science literature effects on second graders concept understanding and collective efficacy - Daloos, Ma. Lara Angela Santos; Paderna, Edwehna Elinore S.; Guerrero, Charlaine G. Guerrero; Alcazar, Marie Yvette C. Alcazar (Quezon City College of Education, University of the Philippines Diliman, 2020)
This study examined the effects of Collaborative-Metacognitive Use of Science Literature Teaching Approach (CMSLTA) on second graders concept understanding and collective efficacy. The CMSLTA refers to a teaching approach that is composed of: (a) grouping of three members with varied reading comprehension ability-beginning, developing, and proficient-with rotating roles-reader, listener, and recorder; (b) use of the Scientific Method Learning Plan incorporated with the three collaborative-metacognitive prompts-planning. Monitoring, and evaluation (TEAL Center, 2012); (c) reading of a science literature; (d) writing a learning journal. It sought to find out whether second graders exposed to the CMSLTA had higher mean posttest concept understanding scores and collective efficacy ratings than those in the Conventional Teaching Approach (CTA). Moreover, the positive influence of collective efficacy on concept understanding was determined. Lastly, this research established whether reading comprehension, as a covariate, moderate the effect of the teaching approach on: (a) concept understanding; and (b) collective efficacy. A quasi-experimental pretest-posttest two-group design was employed on 74 Grade 2 students of an exclusive girls school in Quezon City. One group was exposed to CMSLTA while the other was exposed to the CTA during the second trimester of School Year 2018-2019. Both classes were taught by the researcher. Researcher instruments used in the study was Science Research Associates Reading Laboratory 1b (SRA), Concept Understanding Test (CUT), and Collective Efficacy Scale (CES). The mean pretest and posttest scores/ratings of the two groups in the CUT and CES were subjected to two-tailed t-test and one-tailed t-test for independent samples. Simple linear regression was used to determine whether collective efficacy is a significant predictor of concept understanding. Analysis of covariance (ANCOVA) ascertained whether reading comprehension significantly moderate the effects of the teaching approach on concept understanding and collective efficacy. Findings revealed that students in the CMSLTA group had higher concept understanding mean posttest scores than those in the CTA group. However, results of the linear regression showed that collective efficacy was not a significant positive predictor of concept understanding. Controlling for reading comprehension, the mean posttest scores in the CUT of students in the CMSLTA group was significantly higher than in the CTA group. For collective efficacy, controlling for reading comprehension, the mean posttest rating in the CES of students with SRA total scores greater than 104 in the CTA group was significantly higher than students with SRA total scores greater 104 in the CMSLTA group. Furthermore, the mean posttest rating in the CES of students with SRA total scores less than 104 in the CMSLTA group was significantly higher than students with SRA total score less than 104 in the CTA group. The fusion of the use of science literature and collaborative metacognition in instruction constructively influenced students concept understanding and collective efficacy when all its components and features were reinforced. Additional investigation can be carried out on the effects of CMSLTA to other cognitive and affective domains, subject areas, students in other age groups, co-educational students, and different research locale.
Thesis
Includes bibliographical references.
Keywords: Science -- Study and teaching (Elementary) -- Philippines -- Quezon City; Second grade (Education) -- Philippines -- Quezon City; Cognition in children -- Philippines -- Quezon City